2021
DOI: 10.1002/tal.1843
|View full text |Cite
|
Sign up to set email alerts
|

Determining the optimum outrigger locations for steel tall buildings by using time history analyses

Abstract: Summary The outrigger system is an effective tall building system used at one or multiple locations of high‐rise buildings. It is designed to control and minimize lateral displacement and to increase bending stiffness of the buildings by changing the load transfer mechanism of the structural systems. This paper presents a framework for estimation of the optimum location of the outriggers with structural engineering design approach. Three different sample high‐rise buildings, 35‐story 140‐m, 40‐story 160‐m, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Note that Equation (8) results in a smaller equivalent stiffness than Equation (6), that is, K eq sys < K eq sys . Equations ( 6) and (8) show that as pηχ 1 Ω ! 0,K eq sys !…”
Section: Dynamic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that Equation (8) results in a smaller equivalent stiffness than Equation (6), that is, K eq sys < K eq sys . Equations ( 6) and (8) show that as pηχ 1 Ω ! 0,K eq sys !…”
Section: Dynamic Characteristicsmentioning
confidence: 99%
“…Smith and Coull [4] presented an analytical approach for determining the optimum location of one or more outriggers for minimizing the roof drift under a uniform lateral load and provided design curves for the optimum locations in terms of a nondimensional rigidity parameter that includes the flexural rigidities of the core and outriggers and axial rigidity of perimeter columns. Recently several other researchers have investigated the optimum location of single and multiple outriggers using optimization techniques [5–7] and time history analysis [8] and also presented procedures for seismic design of such structures [9] . These studies and the practical application of conventional outriggers [1] have demonstrated the effectiveness of the system in reducing the lateral deflection of tall buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, an inter-story drift parameter analysis for optimal location of outrigger in tall building reported that under earthquake load, the optimal elevation of outrigger is slightly lower compare to that of wind load [8]. Optimum outrigger position using the dynamic time history analysis reported that the optimal location of outriggers depends on the type of earthquake records [9]. They also concluded that it is more effective to locate the single outrigger at the upper part of the tall building to reduce the lateral displacement at the top of the building.…”
Section: Introductionmentioning
confidence: 99%